Performance and genetics of kenaf (Hibiscus cannabinus L.) for forage yield and quality - Noori, Zahra (2014)
Genetic studies on kenaf (Hibiscus cannabinus L.), a potential forage crop, is necessary to improve kenaf varieties for consumption as a ruminant feed. The main objectives of the present study were to evaluate selected kenaf varieties for forage yield and quality, estimate heritability, heterosis, and genetic parameters involved in the control of forage yield and quality in kenaf populations using generation means analysis, and identify genetic factors associated with kenaf forage yield and quality using SSR markers. Forty kenaf accessions were used to evaluate forage yield and quality. The variations among kenaf accessions were significant for most of the traits measured, except stem-ADF. Accession IX51 was found to have the highest fresh plant yield. IX51 was also found to produce the highest plant dry matter yield followed by G46, which were significantly higher than that of the control variety, V36. Accession 15 produced highest f resh leaf yield, while IX51 showed the highest leaf DM yield. Accessions 75-71, Everglade 41, KK60 and Tainung 1 were found to have with high CP content. Accessions with high plant yields and CP content were used as parents for further evaluation. Further evaluation was conducted on eight selected parental varieties with V36 as the control variety. Accession Cuba 2032 with high plant dry matter yield and leaf dry matter yield and Accessions 75-71 and Everglade 41 with high CP content were selected for further evaluation in a subsequent experiment. Based on the evaluation of performance of the kenaf accessions, 1X51 and Cuba 2032 with highest yields and Accessions 75-71 and Everglade 41 with the highest CP content were selected as parents. These accessions were significantly better than the control variety, V36 and could be used for animal production. Results of correlations indicated that plant yield was positively correlated with yield related components, while it was negatively correlated with leaf to stem ratio. When generation of a population revealed significant differences in a trait, analysis of generation means was employed to study genetics of the trait. The effects of basic generations were significant for all the traits measured in Cross 1 (Cuba 2032 × Accession 75-71) and Cross 2 (1X51 × Everglade 41). F1 mean performances in both crosses were higher than mid-parents values for all traits measured, except days to flowering. Results revealed that both additive and non-additive effects were important in the inheritance of the traits measured in the two crosses, indicating that some of the traits were not simply inherited. Thus, selection could be carried out in later segregating generations. The additive gene effects had a higher contribution than dominant gene effects for most of the traits measured in Cross 1, while dominant gene effects had greater contribution than additive gene effects for some traits measured in Cross 2. High broad-sense heritability for all the traits and high to moderate narrow-sense heritability for most of the traits, except leaf-ADF and stem-ADF, were found in Cross 1. High heritability implies a strong resemblance between parents and offspring with regards to a specific trait. However, in Cross 2, high broad-sense heritability for most of the traits and low to moderate narrow-sense heritability was found for all the traits measured. Positive heterosis for all the traits measured, except for days to flowering, indicates the importance of hybrid vigor for the traits in the two crosses. Negative heterosis for days to flowering, indicates that the hybrid flowered earlier than parents which is good for quality. One hundred and fifty individual F2 plants obtained from the Cuba 2032 × Accession 75-71 cross were used for marker-trait association and to construct a primary genetic linkage map using simple sequence repeats (SSRs). Among SSR markers, five SSRs were found to be closely associated with plant height, leaf to stem ratio, leaf-CP content, stem-CP content, and stem-ADF. Seven polymorphic SSR markers were also randomly distributed on a linkage group with a covering of 128.2 cM. The construction of the kenaf genetic linkage group will be useful for further genetic studies including mapping both qualitative and quantitative traits, marker-assisted selection programs, and comparative genomic analysis.